The Effect of Zeolite Toward Ammonia (NH3) in Tilapia Rearing Media with Recirculation System - Saberina Hasibuan; Syafriadiman Syafriadiman; Muhammad Nandy Syahputra (Universitas Gadjah Mada, 2021)
Culture of Tilapia (Oreochromis niloticus) with high stocking density and feeding can cause a decrease in water quality due to the accumulation of metabolic waste such as ammonia which is toxic for fish rearing. A zeolite filter is needed which can reduce ammonia levels until it is not harmful to fish survival. This research was conducted in February-April 2020 at the Aquaculture Environmental Quality Laboratory, Fisheries and Marine Faculty of Riau University. The purposed of this study was to determine the effect of using zeolite on Ammonia (NH3) and determine the appropriate dose for Tilapia (Oreochromis niloticus) rearing. The research method was a Completely Randomized Design (CRD) one factor with 4 levels of treatment (P0: Control without the use of filters, P1: Use of zeolite 5.68 g/L, P2: Use of zeolite 11.37 g/L, P3: Use of zeolite 17.05 g/L). The appropriate treatment for Tilapia rearing is P3 (Zeolite 17.05 g/L) with TAN value is 0.2616 mg/L, Ammonia 0.0018 mg/L, TAN reduction is 59%, and Survival Rate of fish is 88.88%. The value of water quality during the study were temperature 27-29 oC, pH 6.7-7.0, and DO 6.2-6.9 mg/L.